2021
DOI: 10.1021/acs.jpcc.0c09832
|View full text |Cite
|
Sign up to set email alerts
|

Experimental 13C and 1H Solid-State NMR Response in Weakly Tetrel-Bonded Methyl Groups

Abstract: Like halogens, pnictogens, and chalcogens, group 14 tetrel atoms have the ability to exhibit areas of elevated electrostatic potential on their surfaces (σ-holes) which can engage in noncovalent interactions with electron donors. Evidence for tetrel bonds involving spin-1/2 nuclei, such as 13C, may be found by careful observation of the isotropic chemical shift in solid-state NMR experiments. Here, we study the 13C and 1H solid-state NMR spectroscopic responses to weak tetrel bond formation by examining a seri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 62 publications
(153 reference statements)
2
21
1
Order By: Relevance
“…Unlike most of the other properties, this coupling constant is considerably larger for T1 than for T2. It should be pointed out finally that these various spectral changes are not unique to the FX dimers examined here but are general features of halogen bonds in general and even occur in complexes containing closely related interactions such as chalcogen and pnicogen and even hydrogen bonds. , …”
Section: Discussionmentioning
confidence: 79%
“…Unlike most of the other properties, this coupling constant is considerably larger for T1 than for T2. It should be pointed out finally that these various spectral changes are not unique to the FX dimers examined here but are general features of halogen bonds in general and even occur in complexes containing closely related interactions such as chalcogen and pnicogen and even hydrogen bonds. , …”
Section: Discussionmentioning
confidence: 79%
“…26,47,48 Besides, a change in chemical shift observed from NMR experiments and vibrational stretching frequency obtained from IR and Raman experiments are used as spectroscopic rulers for NCIs. [49][50][51][52][53][54][55][56] The variable temperature NMR/IR and concentration-dependent titrations are significantly helpful in the solution phase to extract thermodynamic parameters such as the enthalpy and entropy of dimerization and complexation. 49,57,58 In addition to the techniques mentioned above, isothermal calorimetric titration (ITC) is also employed to determine the equilibrium constant and other thermodynamic parameters such as Gibbs free energy, entropy and enthalpy.…”
Section: Experimental Methods To Identify Ncis and Measure Their Stre...mentioning
confidence: 99%
“…They showed that the oxygen of THF interacts with the dicyano-substituted carbon atom of the cyclopropane ring via C-bond formation. Recently, Southern et al 52 performed solid-state 13 C-NMR experiments to establish the C-bond in cocrystals based on caffeine and theophylline. Fig.…”
Section: Characterization Techniques Of Ncismentioning
confidence: 99%
“…For example, the signal of the bridging proton moves downfield by several ppm upon formation of a H-bond, and the degree of this shift is closely related to the strength of the bond. There have been several studies in recent years [43][44][45][65][66][67][68][69][70][71] that suggest that these ideas can be extended to halogen and other related noncovalent bonds.…”
Section: Nmr Spectramentioning
confidence: 99%